Sustainable Diving-Based Marine Tourism Product Development Strategy to Enhance Tourist Experience through a Blue Ocean Strategy Approach - I Putu Guna Aditya Yudha; Luh Putu Mahyuni (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
Indonesia’s marine tourism sector is experiencing rapid growth, particularly in diving destinations such as Nusa Penida and Padang Bai. However, increased tourist activity has intensified ecological pressure while many dive operators continue to rely on conventional business models that emphasize recreation rather than sustainability. This study develops a strategic framework for sustainable diving product development using the Blue Ocean Strategy approach, aiming to enhance tourist experience while supporting marine conservation.The study adopts an applied business project research design through field observation, expert interviews, benchmarking of leading conservation-based tourism operators, and review of secondary data. Analytical tools include SWOT–VRIO integration, Porter’s Five Forces, Business Model Canvas, ERRC grid, and strategic mapping. The findings reveal that integrating conservation education, coral-reef restoration programs, transparent governance, digital engagement, and community participation can create new value spaces beyond price-based competition, generating meaningful and differentiated marine-tourism experiences. The research proposes a prototype model of a Sustainable Dive Centre that blends tourism, education, and conservation, offering practical guidelines for operators and policymakers. The model demonstrates how sustainability may function not only as ethical responsibility but as a strategic competitive advantage capable of driving long-term ecological and economic benefits.